(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Information technology can be defined as a combination of computer and telecommunications technologies with other technologies such as hardware, software, databases, network technology, and other telecommunications requirements. The purpose of this study was to describe the challenges encountered by the Information Technology Department in services offered at Loadmanna Inc. Information technology is considered an important tool for improving healthcare services. However, age, civil status, and sex have a significant effect on the IT department at Loadmanna Inc.; ages were more likely to be capable of gaining more knowledge and analyzing problems or challenges in terms of services offered, while civil status and sex indicate that the majority of the respondents were single and male. The challenges encountered indicate that the majority was the software, having an average of 3.88 Strongly Agree. To adopt the right technologies, policy makers should have adequate information about present and future advances. Moreover, the study sought to propose a theory that could explain the conceptualization and measurement of service quality. The relationship between service, consumer satisfaction, and purchase intentions. Primary data for this study was collected from 20 respondents in terms of software, hardware, peopleware, office layout, process, customer service, company income, customer satisfaction, and customer experience.